INFo: Um Sistema de Realidade Aumentada para Publicização de Informações Profissionais Docentes - Araújo, Cristhinny Sarah Pires; Nascimento, Daniela Fernandes do; Carvalho, Sérgio Teixeira de; Souza, Carlos Henrique Rorato; Berretta, Luciana (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
Augmented Reality (AR) combines the real world and virtual elements, expanding perception and interaction with physical reality. This project presents INFo, an application based on Augmented Reality to assist in the maintenance and publication of professional data of teachers at a Computer Science Institute and support students in accessing this information, through an Android mobile application. To evaluate the application, an experiment was carried out which consisted of verifying the behavior of the solution when detecting each plate on four different devices. The proposed application presented promising results, which demonstrate its good performance.